The Path to Salvation Religious Violence from the Crusades to Jihad. - Gregg, Heather Selma (Dulles : Potomac Books Inc., 2014)
In the wake of 9/11, policy analysts, journalists, and academics have tried to make sense of the rise of militant Islam, particularly its role as a motivating and legitimating force for violence against the United States. The general perception is that Islam is more violence-prone than other religions and that scripture and beliefs within the faith, such as the doctrines of jihad and martyrdom, demonstrate the inherently violent nature of Islam. Here, however, Heather S. Gregg draws comparisons across religious traditions to investigate common causes of religious violence. The author sets side.
Ef; g; h; i; j; k; l; m; n; o; p; q; r; s; t; u; v; w; y; z.
Description based on print version record.
Keywords: Violence -- Religious aspects -- History; RELIGION / Comparative Religion; RELIGION / Essays; RELIGION / Reference; Electronic books